RUBRIC-BASED SELF-ASSESSMENT IN INDIAN TERTIARY ESL WRITING: A MIXED METHODS STUDY - S. Kavin Kingston; M. S. Xavier Pradheep Singh (English Education Department at FKIP Nommensen University, 2026)
Rubric-based self-assessment is increasingly recognised as an effective pedagogical approach to support learners’ autonomy and writing proficiency in ESL classrooms. However, such practices remain underexplored in Indian higher education, where teacher-centred evaluation continues to dominate. This study investigates the role of rubric-based self-assessment in shaping confidence, perceptions, and evaluative judgements in writing. An explanatory sequential mixed-methods design was employed with 43 tertiary-level students through a two-week classroom intervention that integrated analytic rubrics into writing tasks. Data were collected using a survey questionnaire, followed subsequently by focus group interviews. The findings indicated that most students reported confidence in identifying and applying rubric criteria and perceived rubrics as a supportive tool for identifying strengths and performance gaps. However, a clear gap emerged between students’ confidence and their ability to self-assess objectively. Although many students were familiar with the rubric structure, they struggled to apply evaluative judgement effectively during revision. Drawing on Tai et al. (2017), this study uses evaluative judgment as an interpretive lens to underscore the importance of scaffolding, guidance and ongoing iterative practice. This study contributes to rubric-based pedagogy by demonstrating the gap between students’ perceived understanding of rubrics and their ability to apply them meaningfully in ESL contexts.